2014
DOI: 10.1007/s00246-014-1051-y
|View full text |Cite
|
Sign up to set email alerts
|

ECG-Synchronized CT Angiography in 324 Consecutive Pediatric Patients: Spectrum of Indications and Trends in Radiation Dose

Abstract: The aim of the study is to describe the spectrum of indications for pediatric ECG-synchronized CT angiography (CTA), the main determinants of radiation exposure, and trends in radiation dose over time at a single, tertiary referral center. The study was IRB approved and HIPAA compliant with informed consent waived. Between 2005 and 2013, 324 pediatric patients underwent ECG-synchronized CTA to evaluate known or suspected cardiovascular abnormalities (109 female, median age 8.1 years). The effective dose (ED) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…We achieved a reasonably low effective radiation dose of 0.36 mSv and the mean CTDI vol of 0.31 mGy using a high-pitch 70-kVp mode. These values are distinctively lower than those in some studies and similar to those in other studies [20,23,24,46,47]. We found no other study that compared [43].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We achieved a reasonably low effective radiation dose of 0.36 mSv and the mean CTDI vol of 0.31 mGy using a high-pitch 70-kVp mode. These values are distinctively lower than those in some studies and similar to those in other studies [20,23,24,46,47]. We found no other study that compared [43].…”
Section: Discussionsupporting
confidence: 85%
“…Nie et al [46] examined 40 children and calculated a mean effective radiation dose of 0.29 mSv for prospectively ECG-triggered CT angiography with a 128-slice dual-source CT scanner with sequential mode. Meinel et al [24] examined a cohort of 259 children with an 80-kVp prospectively ECG-triggered protocol and reported an effective dose of 0.59 mSv (range 0.07-3.5 mSv). These studies demonstrate that the selection of tube potential and tube current, and the method of ECG-synchronization are the main determinants of radiation exposure during ECG-synchronized CT angiography in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTA is being increasingly utilized in patients with congenital heart disease,[3] and its use in neonates on ECMO before surgery has been reported. [4] Unlike DC, CTA can be performed with any type of venous access.…”
Section: Discussionmentioning
confidence: 99%
“…170 A single-institution study showed the median dose for electrocardiographically gated studies in pediatric patients was reduced from 12 to 1.2 mSv between 2005 and 2013. 173 To minimize diagnostic risk, each scan must be tailored to the individual patient and clinical question. Radiation dose for CT angiography has been shown to be 15-fold less than cardiac catheterization in pediatric patients using newer technology and aggressive radiation dose reduction.…”
Section: Strengths and Limitationsmentioning
confidence: 99%